2020
DOI: 10.1016/j.euros.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Retzius-sparing Versus Standard Robotic-assisted Radical Prostatectomy on Penile Shortening, Peyronie’s Disease, and Inguinal Hernia Sequelae

Abstract: Background Retzius-sparing robotic-assisted radical prostatectomy (RS-RARP) has improved urinary function compared with standard robotic-assisted radical prostatectomy (S-RARP). As RS-RARP spares the dorsal vascular complex, pelvic fascia, and anterior abdominal fascia, it may also lower the incidence of “neglected” postprostatectomy sequelae such as penile shortening, Peyronie’s disease, and inguinal hernias. Objective To determine whether there are patient-perceived d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…To our knowledge, our meta-analysis is the most up-to-date and comprehensive. Due to the inclusion of several recent high-quality works of literature (19)(20)(21)(22)(23)(24), we have obtained some more stable results in some outcome indicators that were different from the previous meta-analyses (18,29,30).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…To our knowledge, our meta-analysis is the most up-to-date and comprehensive. Due to the inclusion of several recent high-quality works of literature (19)(20)(21)(22)(23)(24), we have obtained some more stable results in some outcome indicators that were different from the previous meta-analyses (18,29,30).…”
Section: Discussionmentioning
confidence: 81%
“…Of the 14 studies, four were RCTs ( 11 , 12 , 16 , 20 ) and the rest were observational controlled studies ( 13 15 , 17 , 19 , 21 24 , 28 ). Among them, Dalela ( 16 ) and Menon ( 12 ) were from the same randomized controlled study, and Egan ( 24 ) and Kowalczyk ( 23 ) were from the same prospective cohort study. The baseline data of the studies included in our meta-analysis are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In volume 22 of European Urology Open Science , Kowalczyk et al [1] report interesting new data comparing the novel Retzius-sparing robot-assisted radical prostatectomy (RS-RARP) to the standard RARP (S-RARP) approach. In their retrospectively assessed institutional series of 60 RS-RARP and 57 S-RARP procedures performed by a single surgeon, they observed varying rates of “orphaned” postoperative adverse sequelae of RP, such as inguinal hernias, Peyronie’s disease, and penile shortening.…”
mentioning
confidence: 99%